2016
DOI: 10.1080/01496395.2016.1209522
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recycled glass and expanded clay in a dual media configuration for drinking water treatment

Abstract: The aim of this study was to investigate the overall performance of different types of recycled glass media with the optimised coagulation conditions for drinking water treatment. Tests were performed using a laboratory-based filtration unit, with dual filter media configurations and synthetic raw water. The glass media showed comparable performance for both filtration and backwashing and avoided the breakthrough of particles in the effluent. Moreover, the promising performance of the glass media was a slow he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recent research by authors [61] demonstrated that the glass media configurations granted similar performance in relation to that of sand/anthracite in terms of the removal of particles and organic contents. However, a slower head loss development with glass media configurations (both Filtec/Filtralite and AFM/Filtralite) was observed [60]; final head loss values of glass media were more than 60% lower than those obtained by sand/anthracite (Figure 8).…”
Section: Glass-based Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research by authors [61] demonstrated that the glass media configurations granted similar performance in relation to that of sand/anthracite in terms of the removal of particles and organic contents. However, a slower head loss development with glass media configurations (both Filtec/Filtralite and AFM/Filtralite) was observed [60]; final head loss values of glass media were more than 60% lower than those obtained by sand/anthracite (Figure 8).…”
Section: Glass-based Mediamentioning
confidence: 99%
“…Head loss development in four dual media configurations for the entire run with poly-aluminium chloride as coagulant (reprepared using the data from[61]). …”
mentioning
confidence: 99%
“…A typical water treatment plant consists of aeration, coagulation, flocculation, sedimentation, filtration, chlorination and distribution units. The treatment is necessitated by the possible pressure of some impurities such as dissolved gases, dust, minerals, organic matter, microorganisms and other pollutants (Cescon et al, 2016). This research focuses on the filtration unit that removes mainly suspended solids, microbes, mineral, colour and taste.…”
Section: Introductionmentioning
confidence: 99%
“…Filtration is a mechanical or physical operation which is used for the separation of solids from fluids by interposing a medium to fluid flow through which the fluid can pass, but the solids in the fluid are retained. This separation depends on the pore size and the thickness of the medium as well as the mechanism that occurs during filtration (Cescon et al, 2016). Gravity filters consist essentially of an open topped box usually made of concrete, drained at the bottom and partially filled with a filter medium.…”
Section: Introductionmentioning
confidence: 99%